Pengaruh Implementasi Akuntansi Berbasis Akural dan Sistem Pengendalian Internal Terhadap Akuntabilitas Kinerja Instansi Pemerintahan pada Lembaga Manajemen Aset Negara - Gladys Dwika Aprilia; Puja Rizky Ramadhan; Irawan (Economic Reviews Journal, 2025)
The research analysis aims to determine the effect of the implementation of financial-based accounting and internal control systems on the accountability of government agency performance at the State Asset Management Institute. The data analysis technique used is an associative research method with the help of the SPSS version 19 program. This research uses multiple linear regression analysis. The sample in this study was 92 respondents. Primary data collection uses a questionnaire. The research results show that the tcount value is 3.324 > ttable of 1.98 with a significant value of 0.001 <0.05, so the hypothesis H1 is accepted and H0 is rejected, meaning that accounting standards have a partially positive and significant effect on the accountability of the performance of government agencies at the State Asset Management Institute. The test results show a tcount value of 4.554 > ttable of 1.98 with a significant value of 0.000 <0.05, so hypothesis H2 is accepted and H0 is rejected, meaning that the internal control system has a positive and partially significant effect on the accountability of government agency performance at the Asset Management Institute Country. The research results show that accrual-based accounting and internal control systems have a positive and significant effect on performance accountability with a calculated F value of 16.521 which is greater than 3.10 and a significant value of 0.000 which is smaller than 0.05.